Penerapan Edukasi dengan Media Booklet dalam Pengelolaan Kesiapan Peningkatan Manajemen Kesehatan pada Keluarga Berisiko Diabetes Melitus (Studi Kasus): The Application of Education Using Booklets in Managing Health Management Readiness for Families at Risk of Diabetes Mellitus (Case Study) - Mulyati, Sri; Muntamah, Ummu (Jurnal Keperawatan Berbudaya Sehat, 2025)
Diabetes Mellitus (DM) is one of the degenerative diseases with a continuously increasing prevalence in both developed and developing countries. Readiness for improved health management is one of the family issues with DM that can be addressed through education. The research aims to describe the management of health management improvement readiness through education. The type of research is a descriptive case study with a nursing care approach. The research sample was 1 family with a risk of diabetes. Management was carried out for 1 week, with the results of the assessment indicating that the client's family had a history of diabetes, the client stated they always took medication regularly according to the doctor's instructions, and had been regularly participating in the Prolanis program for 3 years. The intervention consisted of health education using a booklet. Implementation included explaining the definition, causes, signs and symptoms, prevention, and both medical and non-medical care, as well as explaining the client's healthy lifestyle with diabetes. Evaluation showed an increase in knowledge for both the client and their family regarding diabetes, and the booklet was effective in improving knowledge. Recommendations for nurses to be more thorough in managing diabetic patients and to make the most of the booklet medium.